Τι λένε οι χρήστες - Σύνταξη κριτικής
Δεν εντοπίσαμε κριτικές στις συνήθεις τοποθεσίες.
Άλλες εκδόσεις - Προβολή όλων
added amount arithmetical becomes binomial called cents changed coefficient combinations common multiple complete constant contain cost cube root denominator difference digits divided dividend division dollars equal equation equivalent Examples Expand Explanation exponent expression Extract factors figures Find Find the value formula fourth fraction geometrical given gives greater Hence highest common divisor imaginary increased indicated interest involving less letters limit logarithm means miles multiplied negative obtained permutations polynomial positive positive integer pounds Principle problem PROCESS progression proportion proved quadratic quotient radical ratio received Reduce remainder represent result Rule second term Simplify Solution Solve square root Substituting subtracted Suggestion surd taken term things third Transposing twice units unknown number variable varies Write written zero
Σελίδα 134 - Multiplying or dividing both terms of a fraction by the same number does not change the value of the fraction.
Σελίδα 403 - The exponent of the power to which a fixed number, called the base, must be raised in order to produce a given number is called the logarithm of the given number.
Σελίδα 41 - A term may be transposed from one member of an equation to the other, provided its sign is changed.
Σελίδα 412 - The logarithm of a quotient is found by subtracting the logarithm of the divisor from that of the dividend.
Σελίδα 212 - ... and if the number is divided by the sum of its digits, the quotient is 21 and the remainder 4.
Σελίδα 230 - ... subtract the product from the dividend, and to the remainder annex the next period for the next dividend.
Σελίδα 410 - The logarithm of the quotient of two numbers is equal to the logarithm of the dividend minus the logarithm of the . divisor.
Σελίδα 62 - The square of the sum of two numbers is equal to the square \ (¿ of the first, plus twice the product of the first and second, plus the J square of the second.